Analisis Perbandingan Kesehatan Bank Central Asia Syariah Dan Bank Rakyat Indonesia Syariah Menggunakan Metode RGEC Periode 2010-2017, - Islamiyati, Dina; Anwar, Moch. Khoirul (Universitas Negeri Surabaya, 2018)
Do self-assessment is the obligation of all banks, the bank's health assessment continues to experience improvement and in this study using the RGEC method (Risk Profile, Good Corporate Governance, Earning, Capital), the assessors are regulated in No. 8/POJK.03/2014, this study compares the health of BCA Syariah and BRI Syariah in 2010-2017. This research uses quantitative descriptive method, secondary data collection, saturated sampling technique. using independent samples t-test. From the results of the study, it can be concluded that the ratio of NPF, GCG, ROA BCA Syariah is superior, the ratio of BRI Sharia FDR is superior, and the CAR ratio is both ranked first.